Development of a parameter-based voice enhancement device (VED) for adaptive multi-rate wideband (AMRWB) codec - Cordel, Macario O., II (2010)
Measurements show that the one-way delay in Next-Generation Networking (NGN) mobile communications typically exceeds the limit for acceptable voice quality. One possible approach to address this issue is to cut down the delay contributed by the suboptimal operation of the Voice Enhancement Device (VED). This research developed and evaluated a parameter-based VED that operates on coded speech rather than on speech waveforms. The information contained in the speech parameters were utilized for voice enhancement such that no transcoding will be needed. For acoustic echo control, the approach is to destroy the speech-like characteristics of the echo by modifying the received parameters. For noise reduction, the traditional procedure is performed except that the approach looks at the codebook gain to estimate the noise level. This approach for VED can be used in NGN to minimize the speech transmission delay, thus, achieving the acceptable voice-quality. Foe objective evaluation, relevant tests based on ITU-T recommendations, showed that both Acoustic echo Control (AEC) and Noise Reduction (NR) Functions passed the ITU-T G.160 specifications. For subjective listening test, NR sections resulted in lower listening-effort mean opinion score (MOSLE). However, improved MOSLE was achieved when both AEC and NR sections were combined.